2022
DOI: 10.3390/app122312426
|View full text |Cite
|
Sign up to set email alerts
|

Voltage Optimization in PV-Rich Distribution Networks—A Review

Abstract: There is a rising trend to integrate different types of distributed generation (DG), especially photovoltaic (PV) systems, on the roofs of existing consumers, who then become prosumers. One of the prosumer impacts is voltage violations, which conventional strategies find hard to solve. However, some prosumers, such as those with PV with inverters in their configurations, can actively participate in voltage optimization. To help find the optimal PV inverter setting with the objective of voltage optimization, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…Finally, addressing the challenges of integrating DERs, such as voltage optimization and overcoming regulatory obstacles, digital solutions emerge as key facilitators. Study [128] focuses on employing PV inverters for voltage control and leveraging optimal power flow tools for enhancing network operations, showcasing effective methods for integrating PV systems into distribution networks.…”
Section: Impact Of Der Integration On Energy Marketsmentioning
confidence: 99%
“…Finally, addressing the challenges of integrating DERs, such as voltage optimization and overcoming regulatory obstacles, digital solutions emerge as key facilitators. Study [128] focuses on employing PV inverters for voltage control and leveraging optimal power flow tools for enhancing network operations, showcasing effective methods for integrating PV systems into distribution networks.…”
Section: Impact Of Der Integration On Energy Marketsmentioning
confidence: 99%
“…The traditional DN control devices, including OLTC, CBs and VRs, preset slow response mechanisms with a limited lifespan due to mechanical parts [4]. However, combined with quick response mechanisms such as PV inverter's reactive power support can achieve promising results in improving DN technical conditions [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of voltage optimization in PV-rich distribution systems is outlined in [18]. The review identified two categories of existing works.…”
Section: Introductionmentioning
confidence: 99%